Mengembangkan Keterampilan Komunikasi dan Kolaborasi Melalui Pembelajaran Aktif dengan Pendekatan MIKiR - Heni Purnamawati (Universitas Batanghari Jambi, 2021)
Communication and collaboration skills are fundamental skills that need to be developed to face the challenges of the globalization era in the 21st century. Based on the results of reflections of learning and observation obtained that communication and collaboration skills that are 21st century 4C skills are still low. This seems, students rarely ask and answer questions from the teacher, the interaction of learning goes in the same direction. Learning that is able to develop communication and collaboration skills is active learning with mikir approach. Active learning with MIKiR approach makes students develop communication and collaboration skills through experience, interaction, communication and reflection activities